2020 Annual trends and outlook report: Sustaining Africa's agrifood system transformation: The role of public policies - Resnick, Danielle; Diao, Xinshen; Tadesse, Getaw (International Food Policy Research Institute, 2020)
Sustained growth and improved governance in Africa’s agriculture sector are critical to meeting the continent’s development goals, including creating decent jobs for youth, nourishing growing cities with healthy foods, promoting resilience, and catalyzing domestic revenue mobilization. The 2020 Annual Trends and Outlook Report (ATOR) from the Regional Strategic Analysis and Knowledge Support System (ReSAKSS) focuses on the policies required to transform African agrifood systems to meet their potential. Chapters provide (1) an in-depth review of the evolution of agricultural sector policies over the last five decades; (2) a systematic analysis of traditional input constraints on agricultural productivity; (3) discussion of policies needed to bolster competitiveness along value chains; and of (4) factors that shape the broader enabling environment needed for agrifood system transformation. The report serves as the official M&E report for the Comprehensive Africa Agriculture Development Programme (CAADP), tracking progress on over 30 CAADP indicators.